2021
DOI: 10.1111/ocr.12546
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a 3D methodology for the evaluation and follow‐up of secondary alveolar bone grafting in unilateral cleft lip and palate patients

Abstract: Orofacial cleft, lip, alveolar bone and/or palate (CLP) is one of the most common congenital birth defects worldwide affecting up to 1 in 700 children. 1 Patients with CLP suffer from negative self-confidence due to functional and aesthetic impairments, therefore, surgical techniques have been introduced to improve both types of impairments such as alveolar bone grafting. 2,3 Secondary alveolar bone grafting (SABG) is usually performed on children at the age of 8-12 years when the canine roots are one-half to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Immediate CBCT scans were performed between 1 and 6 weeks post-operatively to computationally define the grafted region rather than for early outcomes evaluation. 12 Zhang et al 13 examined 60 patients with unilateral clefts of the alveolus who underwent iliac crest bone grafting to determine the ideal timing of dental implant placement. CBCT analysis at 3 months post-operatively revealed that bone mineral density remained stable while bone height declined with time—suggesting that satisfactory bone stock for implant placement is discernable by 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Immediate CBCT scans were performed between 1 and 6 weeks post-operatively to computationally define the grafted region rather than for early outcomes evaluation. 12 Zhang et al 13 examined 60 patients with unilateral clefts of the alveolus who underwent iliac crest bone grafting to determine the ideal timing of dental implant placement. CBCT analysis at 3 months post-operatively revealed that bone mineral density remained stable while bone height declined with time—suggesting that satisfactory bone stock for implant placement is discernable by 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar bone grafting (ABG) was of great importance in the cleft lip and palate team approach. It could not only fill the cleft area but also support the alar base, close oroantral fistulae, and help the eruption of canines within the cleft area [ 5 ]. ABG included primary alveolar bone grafting (PABG) and secondary alveolar bone grafting (SABG).…”
Section: Introductionmentioning
confidence: 99%
“…When the requirement of bone is small, the mandibular angle can be the donor site, so there is no need for an extra-oral incision [ 15 ]. However, to obtain the accurate cleft volume, most researchers segmented the maxilla and filled the clefts through threshold division and manual modification, time-consumingly and laboriously [ 5 , 16 ]. Machine learning is a branch of artificial intelligence that uncovers patterns in data automatically and then applies the detected patterns for future data prediction [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no consensus methods to analyse the alveolar bone reconstruction. 7 Very recently, Kamperos et al, in 2020, proposed a new score measuring the height and width of the alveolar bone as well as the level of the nasal floor. 8 They compared it with the usual 2D scores.…”
mentioning
confidence: 99%
“…While their methods are becoming more accurate, few analyse the alveolar bone as a whole and some are tedious to apply in daily practice. There is currently no consensus methods to analyse the alveolar bone reconstruction 7 …”
mentioning
confidence: 99%